Investigating the modulatory effects of lactoferrin on depressed rats through 16S rDNA gene sequencing and LC–MS metabolomics analysis - Jing Zhang; Hongmei Xin; Wuji Wang; Yanyi Li; Riga Wu; Lisi Wei; Si Su; Xiaohong Wang; Xiujuan Wang; Xiaojuan Wang; Li Li; Rilebagen Hu (Scientific Reports)
Abstract Lactoferrin is a natural multifunctional glycoprotein with potential antidepressant-like effects. However, the mechanism of its antidepressant effect has not been explored from the perspective of gut flora metabolism. Therefore, we employed both 16S rDNA gene sequencing and LC–MS metabolomics analysis to investigate the regulatory effects and mechanisms of lactoferrin in a rat model of depression. After one week of acclimatization, twenty-four 7-week-old male Sprague–Dawley rats were randomly and equally assigned into three groups: the control group, the model group, and the lactoferrin intervention group. The control group rats were housed under standard conditions, while the rats in the model and lactoferrin intervention groups were individually housed and exposed to chronic unpredictable mild stress for 44 days simultaneously. The lactoferrin intervention group was provided with water containing 2% lactoferrin (2 g/100 ml). Behavioural tests were conducted at week 7. Upon completion of the behavioral tests, the rats were anesthetized with isoflurane, humanely euthanized using a rat guillotine, and tissue samples were collected for further experiments. The results indicated that lactoferrin intervention led to an increase in sucrose solution consumption, horizontal movement distance, number of cross platforms, and residence time in the target quadrant. Additionally, it resulted in an increase in jejunal tight junction protein ZO-1 expression and a suppression of serum expression of inflammatory factors, Lipopolysaccharide and Diamine oxidase. In summary, lactoferrin can regulate the metabolic disorder of intestinal flora, reduce intestinal permeability, and further regulate the metabolic balance of hippocampal tissues through the microbiota-gut-brain axis. This process ultimately alleviates the depression-like behavior in rats.